EVALUASI USABILITY SISTEM BORDER CONTROL MANAGEMENT DENGAN METODE SYSTEM USABILITY SCALE DI TEMPAT PEMERIKSAAN KEIMIGRASIAN MOTAAIN - Emris Yeverson Kaja Jade (Universitas Nusa Cendana, 2022)
The Border Control Management system is a technology-based management system that oversees national border areas and handles immigration inspection activities for people who will leave or enter the Republic of Indonesia through the Checkpoint. However, if this system does not work optimally, it will interfere with the implementation of immigration duties. Therefore, it is necessary to measure the usability of the Border Control Management System. Usability is a quality measure that is able to assess the ease with which a system or website interface can be used by users by considering certain criteria. One type of usability measurement is the System Usability Scale which is applied using a questionnaire. This study aims to determine the results of the usability of the Border Control Management System using the System Usability Scale method. The type of data obtained from this study is primary data, namely the respondents' answers to the questionnaire given. In sampling, the technique used is a sampling technique used to make samples with all members of the population used as samples. The results of this study indicate that the usability value of the Border Control Management System obtained using the System Usability Scale is 76.67. This shows that the category of acceptance of the use of the BCM System is “acceptable” which means that the BCM System is acceptable to the user. Furthermore, the usability rating of the BCM System is included in the “Good” category and the usability scale is in the “B” category.